Environmental policy diffusion and lobbying - Joschka Gerigk; Ian MacKenzie; Markus Ohndorf (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
In this article, we examine the regulation of pollution in open economies when the regulator is influenced by special interest groups. In a setting with free trade, we identify conditions under which a country may unilaterally adopt the stricter regulatory standards of its competitors. In our model, two lobby groups - representing industrial and environmental special interests - influence their government's policy decision. Their lobbying efforts not only depend on the domestic policy, but also on environmental regulation abroad. We find that both market structure and the characteristics of the pollutant are crucial determinants of the political equilibrium: given a local pollutant, the probability of convergence of environmental policies is increasing in the stringency of regulation abroad when product supply is relatively inelastic. This effect is reversed in the case of transboundary pollution. We also extend our framework to cases of imperfect competition.
Keywords: Q50; H73; D72; 330